El Impacto de los Factores Técnicos en la Calidad del Desarrollo de los Sistemas de Información para la Toma de Decisiones y Uso por el Usuario - JOSE MELCHOR MEDINA QUINTERO (2017)
This research analyzes the impact of some technical factors (Programmer Skills, Data Source and Technology Infrastructure) in the quality of development and operation of the information systems for the Decision Making and System Use by the user, based on a research model designed for this aim. The empirical study is carried out in six Higher Education Institutions in the northeast of Mexico (94 questionnaires) by means of a statistical tool known as Partial Least Squares. The results show that Programmer Skills and Information Quality are the elements with most impact, mainly in the Decision Making (60% of explained variance).